1998
DOI: 10.1063/1.368853
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and Raman study of compensation effects in Mg-doped GaN epilayers

Abstract: The compensation of Mg-doped GaN is systematically studied by low-temperature photoluminescence and Raman spectroscopy using a series of samples with different Mg concentrations. Strongly doped samples are found to be highly compensated in electrical measurements. The compensation mechanism is directly related to the incorporation of Mg. Three different deep donor levels are found at 240±30, 350±30, and 850±30 meV from the conduction band, each giving rise to deep unstructured donor-acceptor pair emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 12 publications
10
56
0
Order By: Relevance
“…The origin of this band is still not completely understood and recent experimental results indicate that it might consist of more than one emission band [5,22]. Most researchers agree that the blue band is caused by a transition between a deep localized donor and an acceptor state (likely a Mg-related acceptor) [4,5,23]. Both theoretical [4,24] and experimental [4,5] studies concluded that the incorporation of high Mg concentrations is accompanied by a formation of additional deep donors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The origin of this band is still not completely understood and recent experimental results indicate that it might consist of more than one emission band [5,22]. Most researchers agree that the blue band is caused by a transition between a deep localized donor and an acceptor state (likely a Mg-related acceptor) [4,5,23]. Both theoretical [4,24] and experimental [4,5] studies concluded that the incorporation of high Mg concentrations is accompanied by a formation of additional deep donors.…”
Section: Resultsmentioning
confidence: 99%
“…5). The origin of this band is still not completely understood and recent experimental results indicate that it might consist of more than one emission band [5,22]. Most researchers agree that the blue band is caused by a transition between a deep localized donor and an acceptor state (likely a Mg-related acceptor) [4,5,23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The shape of the observed DAP related peaks changes between the different samples. The lineshape of this band depends on the concentration of Mg, as a consequence of the complexity of the Mg acceptor configuration in the GaN lattice [36], and the difficulty to set up the conditions for the optimum Mg doping. Recently, different DAP transitions associated with three different Mg-related acceptor levels have been reported [37].…”
Section: Experimental and Samplesmentioning
confidence: 99%